2006
DOI: 10.1185/030079906x104731
|View full text |Cite
|
Sign up to set email alerts
|

The impact of migraine on daily activities: effect of topiramate compared with placebo

Abstract: Improvements in patient-reported outcomes specific for migraine (measured by the MSQ) were significantly better for patients receiving topiramate than for those receiving placebo. Improvements in the prospectively selected MSQ and SF-36 domains were significantly correlated with the decrease in mean monthly migraine frequency observed with topiramate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Such experiments have not been carried out, although a significant effect of migraine medication with triptans versus placebo on self-reported work productivity was documented in a randomized clinical trial (58) and significant before-after reductions in sickness absence were documented in several open-label studies of migraine treatment in workplace samples (59-62). These results suggest that large-scale workplace effectiveness trials are warranted for workers with frequent or severe migraines.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments have not been carried out, although a significant effect of migraine medication with triptans versus placebo on self-reported work productivity was documented in a randomized clinical trial (58) and significant before-after reductions in sickness absence were documented in several open-label studies of migraine treatment in workplace samples (59-62). These results suggest that large-scale workplace effectiveness trials are warranted for workers with frequent or severe migraines.…”
Section: Discussionmentioning
confidence: 99%
“…[38,39] Clinical trials have demonstrated that the antiepileptic medications topiramate and divalproex sodium are effective for migraine prophylaxis. Topiramate is efficacious across a broad range of migraine frequencies [40][41][42] and has been associated with improvements in the performance of daily activities and QOL in episodic [43][44][45] and chronic migraine, as assessed by the MSQ. [46] The most common adverse effects associated with topiramate treatment include paraesthesia, fatigue, appetite loss and difficulty concentrating.…”
Section: The Role Of Migraine Preventionmentioning
confidence: 99%
“…Topiramate 100 mg per day also improves daily activity outcomes 46 . This post hoc analysis involved 2 validated quality‐of‐life instruments – one disease‐specific, the Migraine‐Specific Questionnaire (MSQ), and one nondisease‐specific, the SF‐36.…”
Section: Topiramatementioning
confidence: 99%